Interconnect materials enabling IGBT modules to achieve stable short circuit failure behavior - Li, Jianfeng; Yaqub, Imran; Corfield, Martin; Johnson, Christopher Mark (Institute of Electrical and Electronics Engineers, 2017)
Insulated gate bipolar transistor (IGBT) modules, which can fail to stable short-circuit mode, have major applications in electricity network-related fields. Sn-3.5Ag solder joints and sintered Ag joints for the die attachment and Mo, Cu, Sn-3.5Ag, Al, and Ag foils for the top side insert (TSI) material in press pack like single IGBT samples have been investigated using overcurrent and current passage tests. The results reveal that Sn-3.5Ag solder joints in combination with Sn-3.5Ag, Al, or Ag foils can be employed to achieve stable short-circuit failure mode, where the best results are achieved with Ag foils. This can be attributed to the formation of conductive networks/channels through the failed IGBT and good alignment between the residual TSI material and the failed IGBT.